Optimization of Two-Dimensional Photonic Crystals with Artificial Bee Colony Algorithm - Da Silva, Mailson G. [UNESP]; Malheiros-Silveira, Gilliard N. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
We applied the Artificial Bee Colony algorithm for the complete band gap maximization of a two-dimensional photonic crystal. The band diagram and band gap calculation were carried out by the software MIT Photonic Bands, and these results were used in the algorithm's fitness function. The optimum structure was compared to the literature which used genetic algorithm, and it was observed a raise in the complete band gap of the photonic crystal.